Serologic survey on some transmissible diseases among wild boars and free ranging pigs in Sardinia - Firinu A.; Ponti M.N.; Patta C.; Oggiano A.; Ruiu A.; Cabras P.; Maestrale C.; Cossu P.; Pintore A. (Tradition and innovation in Mediterranean pig production, 2000)
An organized sampling was established in wild boars and free ranging pigs. The survey regarded infections concerning either economic aspects, e.g., Aujeszky disease, or zoonosis, e.g., Leptospirosis and Brucellosis as well as Trichinellosis, because of its transmissibility through swine, meat and meat products. Up to now, negative results for Trichinellosis were found. Instead, a large spreading of the other pathologies in both domestic and wild swines was observed. For Brucellosis it is important to establish whether the high rate of positive sera is specific for brucella and what biovar is involved. This kind of survey could be very helpful in control programs and pathology prevention.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)